2016
DOI: 10.1136/annrheumdis-2016-eular.6109
|View full text |Cite
|
Sign up to set email alerts
|

SAT0237 Nailfold Capillaroscopy Findings in Scleroderma Patients – Prognostic Implications

Abstract: BackgroundNailfold capillaroscopy (NCP) is a useful tool for the diagnosis and follow-up of systemic rheumatic diseases and represents one of the best methods to evaluate microvascular abnormalities.ObjectivesTo characterize NCP findings of patients with Systemic Sclerosis (SSc), and understand how NCP associates with the presence of digital ulcers, gastrointestinal involvement, pulmonary arterial hypertension (PAH) and interstitial lung disease (ILD).MethodsNCP findings of adult patients with SSc followed-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The NT-proBNP values were significantly correlated with reduced capillary density and with the se- verity of nailfold capillaroscopic pattern. Higher values of NT-proBNP were more common in patients with extended avascular areas (37). Markusse et al identified that a more severe nailfold capillaroscopic pattern was associated with the risk for interstitial lung disease (OR=1.34, 95% CI 1.04-1.74), reduced DLCO (OR=1.52, 95% CI 1.17-1.98), increased PASP (OR=2.33, 95% CI 1.01-5.39), and increased NT-proBNP (OR=1.70, 95% CI 1.09-2.64) (38).…”
Section: Figure 1 Pearson Correlation Between Pasp and Nt-probnp In mentioning
confidence: 91%
“…The NT-proBNP values were significantly correlated with reduced capillary density and with the se- verity of nailfold capillaroscopic pattern. Higher values of NT-proBNP were more common in patients with extended avascular areas (37). Markusse et al identified that a more severe nailfold capillaroscopic pattern was associated with the risk for interstitial lung disease (OR=1.34, 95% CI 1.04-1.74), reduced DLCO (OR=1.52, 95% CI 1.17-1.98), increased PASP (OR=2.33, 95% CI 1.01-5.39), and increased NT-proBNP (OR=1.70, 95% CI 1.09-2.64) (38).…”
Section: Figure 1 Pearson Correlation Between Pasp and Nt-probnp In mentioning
confidence: 91%
“…L.C. Teixeira, in two different studies 17,18 revealed the association between stages and organ involvement. The first study was conducted from January 2013 to December 2015.…”
Section: Reported Prognostic Associations Of Nvc In Subtypes Identificationmentioning
confidence: 97%
“…L.C. Teixeira, in two different studies 17,18 revealed the association between stages and organ involvement. The first study was conducted from January 2013 to December 2015.…”
Section: Reported Prognostic Associations Of Nvc In Subtypes Identificationmentioning
confidence: 97%